CHEMICAL APPLICATIONS AFFECTED DORMANCY BREAKING IN ‘MODI’ APPLE CULTIVAR UNDER SUBTROPICAL CONDITIONS - Burhanettin Đmrak; Ayzin B. Küden; Ali Küden; A. Kadir Sarier; Berken Çimen (Acta Scientiarum Polonorum: Hortorum Cultus, 2016)
The winter chill is essential for most fruit crops. Fruit trees require a certain number of chill hours, also called chill units, each winter to produce fruits in the next summer. Insufficient chilling accumulation during winter period usually results in blooming disorders and decreases the fruit yield of deciduous fruit trees. Dormancy can be broken by using chemicals, such as Dormex. In recent years Dormex has been forbidden in some countries, including Turkey since it was found to be carcinogenic to human beings. This situation raised a necessity to find alternative chemicals to Dormex to be used in subtropical climate regions. For this purpose, six years old trees of ‘Modi’ apple scions (Malus sylvestris, Mill) grafted on Malling-Merton M9 rootstocks were sprayed with 6% Erger (total nitrogen, 15.0%; ureic nitrogen, 6.1%; nitric nitrogen, 5.8%; ammoniacal, 3.1%; water soluble calcium oxide, 4.7%), hydrogen cyanamide 4% (Dormex) and potassium nitrate 8% (KNO3 ) for breaking dormancy of the buds during 2011–2013. Calculating the chilling hours below 7°C and chill unit (CU) values during the experimental winter periods, 497 to 828 h and 357 to 467 CU of chilling durations were obtained under subtropical conditions of Adana (36°56 12'04''N. 35° 33'53.46''E ). Modi broke endodormancy of the buds on 20 February 2012 with the accumulation of 375 CU and 550 h. The effects of dormancy breaking agents on bud break, fruit set and fruit quality were investigated. Erger markedly advanced bud-break and increased the final fruit set, quality and yield in comparison with the other treatments and control.